(untitled) (PERcursos Linguísticos, 2020)
This article aims to discuss the relationship between the body and the party, using the studies of Mikhail Bakhtin as the main theoretical contribution. While the body, in dialogical relations with the other, survives looking for possibilities to exist and resist against chaos, the party appears dressed in the colors of the rainbow and hopelessly in love with its gods. Although the central discussions of this article are located in the historical context of the Middle Ages, their reverberations contribute to the understanding, today, of the phenomena of language related to the body and the party, which on the eve of the second decade of the 21st century they are obliged to wear a crown of thorns and dance to the sound of the trumpets of the Apocalypse.